Application of software to study the impact of transportation sectors' greenhouse gas emissions reduction on climate change. Issue 6 (31st October 2016) - Kalita, Neelnayana; Xu, Zonghua; Kumar, Ashok
Abstract : The study of environmental pollution has been significantly aided through computerized tools and models over the last several decades. There are enormous social and economic benefits of using software for studying the climatic impact of the greenhouse gas (GHG) emissions. This paper presents an approach to examine the climatic impact of emissions from the transportation sector by identifying available software (namely, MOVES, GREET, and mixed‐use trip generation model) for projecting future GHG emission levels. This process is followed by the quantification of GHG emissions with variations in the temperature considering that temperature change at any given geographical region directly influences the projections of climate change. This study presents the application of relevant software in examining the various GHG emission reduction strategies, which can play an important role in understanding possible variations in the projected temperature variations for the transportation sector within a geographical region. © 2016 American Institute of Chemical Engineers Environ Prog, 35: 1559–1565, 2016